Instruments for evaluation and treatment of Pressure Injuries: literature review (Research, Society and Development, 2023)
Objective: to characterize the technologies/instruments for the assessment and treatment of pressure injuries built and validated in the last five years. Methods: an integrative review carried out in six stages, with the following question: “How are the instruments for the assessment and treatment of pressure injuries constructed and validated in the scientific literature of the last five years?”, using the databases Nursing Database ; Latin American and Caribbean Literature in Health Sciences and Scientific Electronic Library Online and Medical Literature Analysis and Retrieval System Online; and as descriptors: pressure ulcer, nursing and technology. Complete articles were included, in Portuguese and English, published in the last 5 years and incomplete publications, repeated articles and unrelated to the central theme and objective of the study were excluded. By applying filters based on inclusion and exclusion criteria, reading and initial analysis, six articles made up the final sample. Results: the construction and validation studies follow methodological rigor regarding the evaluation and validation processes for use in care practice or health education. Two categories emerged for analysis: light and light-hard technologies for assessment and treatment of pressure injuries; and media, applications, and the use of artificial intelligence (AI) as tools for assessing and treating pressure injuries. Conclusion: it was possible to characterize the constructed and validated technologies/instruments for the assessment and treatment of pressure injuries. Technologies developed on digital platforms, applications and web resources are emerging among the tools recently developed by nurses for the management of pressure injuries.